Chapter 6 Teachers' well-being, social and emotional competences, and reflective teaching - Ferreira, Marco (Taylor & Francis, 2022)
Teacher's well-being has become a priority in the last two decades. If we believe that schools have a role in promoting the mental health and students' well-being, we must first recognize and address the raising matter of teachers' mental health and well-being. Research shows that there is a straight connection between teachers' well-being and their social and emotional competences (Collie, 2017; Schonert-Reichl, 2017). Reflective teaching is the tool that we use to develop a model of intervention to promote teachers' well-being, and the model is supported on a social constructivist perspective. Reflective teaching is a process through which teachers think over their teaching practices, analysing how something had been taught and how the practice might be improved or changed for better learning outcomes. The teacher's continuous training model for professional development and well-being enlarges the emphasis on teachers' practices/experiences and connect them with meaningful situations, accentuating social and emotional competences to improve teachers' professional attainment and effectiveness. Processes of self-observation and self-evaluation based on reflective inquiry, and reflection on practice support the practical application of the model. Research also shows that well-being and job satisfaction strongly influence teachers' behaviours, which affect classroom climate and students' achievement as well (Collie et al.,2015; Van Dick et al., 2007). This teacher's continuous training model agglomerates several theoretical constructs relevant to pedagogy and may constitute a good practice for the promotion of teachers' professional development and well-being.